2020
DOI: 10.1088/2053-1583/abb876
|View full text |Cite
|
Sign up to set email alerts
|

Brightening of spin- and momentum-dark excitons in transition metal dichalcogenides

Abstract: Monolayer transition metal dichalcogenides (TMDs) have been in focus of current research, among others due to their remarkable exciton landscape consisting of bright and dark excitonic states. Although dark excitons are not directly visible in optical spectra, they have a large impact on exciton dynamics and hence their understanding is crucial for potential TMD-based applications. Here, we study brightening mechanisms of dark excitons via interaction with phonons and in-plane magnetic fields. We show clear si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Experiments have shown that the application of a magnetic field can brighten the dark exciton states. [26][27][28][29][30] Plasmon induced brightening of dark excitons in TMDC monolayer has also been reported. [31] In doped TMD layers, trions (charged excitons) are also formed along with excitons.…”
Section: Introductionmentioning
confidence: 85%
“…Experiments have shown that the application of a magnetic field can brighten the dark exciton states. [26][27][28][29][30] Plasmon induced brightening of dark excitons in TMDC monolayer has also been reported. [31] In doped TMD layers, trions (charged excitons) are also formed along with excitons.…”
Section: Introductionmentioning
confidence: 85%
“…As a result, intralayer excitons with electrons and holes being localized in the same monolayer, can be dipole allowed (bright) with in-plane (IP) or out-of-plane (OP) transition dipole moments, or generally forbidden (dark) depending on the quantum numbers of the contributing single particle states [16,17]. In monolayer WS 2 , WSe 2 , as well as charge-neutral MoS 2 , the energetic splitting between bright and dark excitons has been reported to be positive, which implies that the excitonic ground state transition is considered to be momentum or spin forbidden (dark) [17][18][19][20][21][22][23][24]. In contrast, the energetically lowest exciton transition in MoSe 2 is reported to be bright with an in-plane (IP) optical dipole moment [23,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, dark excitons can accumulate if their energies are below the energies of bright excitons, as predicted for MoS 2 , WS 2 , and WSe 2 [21]. The rich landscape of dark excitons is still relatively unexplored (one exception is momentumallowed but spin-forbidden states that can be brightened by a magnetic field [22][23][24] or by coupling with surface plasmon-polaritons [25]) due to a lack of effective approaches for directly probing dark states [26][27][28]. This barrier has recently been lifted by the development of a pump-probe photoemission technique that can reveal the spatial, temporal, and spectral dynamics of both bright and dark excitons [29], which has opened a new area of dark excitonics in TMD monolayers and beyond.…”
Section: Introductionmentioning
confidence: 99%